SaR Resource Management Based on Description Logics Technology for Emergency Response - Pottebaum, Jens; Konstantopoulos, Stasinos; Koch, Rainer; Paliouras, Georgios (Mobile Response, First International Workshop on Mobile Information Technology for Emergency Response, Mobile Response 2007, Sankt Augustin, Germany, February 22-23, 2007, Revised Selected Papers)
Keywords: Ver{\

Cleavage in the γ-subunit of the epithelial sodium channel (ENaC) plays an important role in the proteolytic activation of near-silent channels - Diakov, Alexei; Bera, Katarzyna; Mokrushina, Marianna; Krueger, Bettina; Korbmacher, Christoph (The Journal of Physiology)
The mechanisms by which proteases activate the epithelial sodium channel (ENaC) are not yet fully understood. We investigated the effect of extracellular proteases on rat ENaC heterologously expressed in Xenopus laevis oocytes. Application of trypsin increased ENaC whole-oocyte currents by about 8-fold without a concomitant increase in channel surface expression. The stimulatory effect of trypsin was preserved in oocytes expressing alphagamma-ENaC, but was abolished in oocytes expressing alphabeta-ENaC. Thus, the gamma-subunit appears to be essential for channel activation by extracellular proteases. Site-directed mutagenesis of a putative prostasin cleavage site in the extracellular loop of the gamma-subunit revealed that mutating the 181Lys residue to alanine (gammaK181A) increases ENaC baseline whole-oocyte currents, decreases channel surface expression, and largely reduces the stimulatory effect of extracellular proteases (trypsin, chymotrypsin and human neutrophil elastase). In single-channel recordings from outside-out patches we demonstrated that the gammaK181A mutation essentially abolishes the activation of near-silent channels by trypsin, while a stimulatory effect of trypsin on channel gating is preserved. This apparent dual effect of trypsin on channel gating and on the recruitment of near-silent channels was confirmed by experiments using the beta518C mutant ENaC which can be converted to a channel with an open probability of nearly one by exposure to a sulfhydryl reagent. Interestingly, the gammaK181A mutation results in the spontaneous appearance of a 67 kDa fragment of the gamma-subunit in the plasma membrane which can be prevented by a furin inhibitor and also occurs after channel activation by extracellular trypsin. This suggests that the mutation promotes channel cleavage and activation by endogenous proteases. This would lower the pool of near-silent channels and explain the constitutive activation and reduced responsiveness of the mutant channel to extracellular proteases. We conclude that the mutated site (K181A) affects a region in the gamma-subunit of ENaC that is functionally important for the activation of near-silent channels by extracellular proteases.

Theoretical study of the localization of excess electrons at the surface of ice - Hermann, A; Schwerdtfeger, P; Schmidt, Wolf Gero (Journal of Physics: Condensed Matter)

Involving the User in Semantic Search - Ngonga Ngomo, Axel-Cyrille; Schumacher, Frank (Human Interface and the Management of Information. Methods, Techniques and Tools in Information Design, Symposium on Human Interface 2007, Held as Part of HCI International 2007, Beijing, China, July 22-27, 2007, Proceedings Part I)

Buying Cheap is Expensive: Hardness of Non-Parametric Multi-Product Pricing - Briest, Patrick; Krysta, Piotr (Proceedings of the 18th ACM-SIAM Symposium on Discrete Algorithms (SODA))

Protein intake during the period of complementary feeding and early childhood and the association with body mass index and percentage body fat at 7 y of age. - Günther, AL; Buyken, Anette; Kroke, A (Am J Clin Nutr)

Breakfast glycemic index affects subsequent daily energy intake in free-living healthy children. - Buyken, Anette; Trauner, K; Günther, AL; Kroke, A; Remer, T (Am J Clin Nutr)

How early dietary factors modify the effect of rapid weight gain in infancy on subsequent body-composition development in term children whose birth weight was appropriate for gestational age. - Karaolis-Danckert, N; Günther, AL; Kroke, A; Hornberg, C; Buyken, Anette (Am J Clin Nutr)

Early protein intake and later obesity risk: which protein sources at which time points throughout infancy and childhood are important for body mass index and body fat percentage at 7 y of age? - Günther, AL; Remer, T; Kroke, A; Buyken, Anette (Am J Clin Nutr)

Pattern of beverage consumption and long-term association with body-weight status in German adolescents – results from the DONALD study - Libuda, Lars; Alexy, Ute; Sichert-Hellert, Wolfgang; Stehle, Peter; Karaolis-Danckert, Nadina; Buyken, Anette; Kersting, Mathilde (British Journal of Nutrition)
In the present study the relationship between the consumption of different beverage groups and body-weight status in 5 years of study participation in German adolescents was investigated. We used anthropometric and dietary data from 3 d weighed records of 244 subjects between 9 and 18 years of age participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study. Only subjects with at least four out of six possible weighed dietary records were considered. A repeated-measures regression model (PROC MIXED) was used to analyse the effect of beverage consumption on body-weight status. BMI standard deviation scores (BMI-SDS) and body fat percentage (%BF) were chosen as the dependent variables. In boys, energetic beverage consumption was not associated with BMI-SDS or %BF, neither cross-sectionally nor prospectively. In girls, baseline consumption of energetic beverages did not predict baseline BMI-SDS, baseline %BF, or change in either variable over the study period. However, an increase in energetic beverage consumption over the study period was associated with an increase in BMI-SDS (+0.070 SDS/MJ increase in energetic beverage consumption; P = 0·01). Separate consideration of regular soft drinks and fruit juices revealed that, in girls, BMI-SDS increased with increased fruit juice consumption (+0·096 SDS/MJ increase in fruit juice consumption; P = 0·01), and to a lesser extent with regular soft drink consumption (+0·055 SDS/MJ increase in regular soft drink consumption; P = 0·08). In conclusion, these results suggest that an increase in energetic beverage consumption may result in weight gain, at least in adolescent girls.

DONALD News: Zuckerhaltige Getränke und Übergewicht bei Kindern. - Libuda, Lars; Alexey, U. (Monatsschriften Kinderheilkunde)

Dietary Glycemic Index, Glycemic Load, Fiber, Simple Sugars, and Insulin Resistance: The Inter99 Study: Response to Lau et al. - Buyken, Anette; Liese, A. D. (Diabetes Care)

Type 2 diabetes mellitus and risk of coronary heart disease: results of the 10-year follow-up of the PROCAM study - Buyken, Anette; von Eckardstein, Arnold; Schulte, Helmut; Cullen, Paul; Assmann, Gerd (European Journal of Cardiovascular Prevention & Rehabilitation)

Zum Umgang mit Vielfalt im haushaltsbezogenen Unterricht - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Vermittlung von Konsum- und Finanzkompetenzen für Kinder und Jugendliche - Möglichkeiten und Grenzen pädagogischen Handelns - Schlegel-Matthies, Kirsten (Der pädagogische Blick. Zeitschrift für Wissenschaft und Praxis in pädagogischen Berufen)

REVIS - Moderne Ernährungs- und Verbraucherbildung - Oepping, A.; Schlegel-Matthies, Kirsten

Interactive Refinement of a Material Flow Simulation Model by Comparing Multiple Simulation Runs in one 3D Environment - Fischer, Matthias; Laroque, Christoph; Huber, Daniel; Krokowski, Jens; Mueck, Bengt; Kortenjan, Michael; Aufenanger, Mark; Dangelmaier, Wilhelm (European Simulation and Modelling Conference (ESM 2007))
The validation of material flow models as well as the selection of promising strategies for the generation of a successful experiment plan is a time-consuming process. A new approach is presented, which supports the simulation expert in his working process by giving him the opportunity to modify the simulated simulation run and afterwards compare the effects of his modification with the original setting, online and in one user interface, implemented by switching the visualizations between the simulation runs or opening up to 5 parallel 3D windows. The method developed therefore clones existing simulation runs online and allows the navigation within these existing simulation runs. The method has been implemented and is validated by a test model, which describes in detail the new working process of a modeler. New research questions are derived from this work, which will define following working steps.

Ein ganzheitlicher Ansatz zur immersiven 3D-Materialflusssimulation innerhalb der Digitalen Fabrik - Dangelmaier, Wilhelm; Laroque, Christoph; Fischer, Matthias (Augmented & Virtual Reality in der Produktentstehung)

Outage probability analysis of cooperative transmission protocols without and with network coding: inter-user channels based comparison - H. Woldegebreal, Dereje; Valentin, Stefan; Karl, Holger (Proceedings of the 10th International Symposium on Modeling Analysis and Simulation of Wireless and Mobile Systems, MSWiM 2007, Chania, Crete Island, Greece, October 22-26, 2007)

En route vers un but commun: Besonderheiten der Kommunikation zwischen Sprachlernern und Implikationen für die Fremdsprachendidaktik. - Behrent, Sigrid (Band zur Tagung: Multilateralität und europäischer Bildungsauftrag, Bremen (20.-22. Juni 2006))